Severe Tooth Decay and Erosion Regarding Cariogenic Habits: A Rampant Caries Case Report - Tezel, Huseyin; Atalayin, Cigdem; Kemaloglu, Hande; Cinarcik, Serhat (The Journal of Dentists, 2017)
Sugars and soft drinks have cariogenic potential concerning their acidogenic structure. High consumption of these cariogenic food and drinks for prolonged time may result in dental erosion and severe tooth decay. The aim of this report is to present a patient who had rampant caries and aesthetic problems resulting from his cariogenic habits. A 22-year-old man referred to our clinic with rampant caries. The patient who was stressed and anxious had also aesthetic concerns. Although he had no systemic-health problems, his oral hygiene was extremely poor. The diagnosis was severe tooth decay, multiple erosive lesions at different stages and concomitant gingivitis. The anamnesis revealed the history of consuming 4-5 L cola and 30-40 pieces of peppermint every day during the past 4 years. The patient also reported that he had nausea reflex and constantly chewed mentholated gum to inhibit his discomfort. The full-mouth rehabilitation was achieved with a multidisciplinary approach within the limitation of the patient cooperation. In the case of high intake of acidogenic food and drinks that caused severe tooth decay, the treatment procedures experienced were challenging. Thus, patient education/motivation and counselling on cariogenic habits were considered in multidisciplinary treatment planning for the prosperous prognosis of the case.